2012
DOI: 10.1111/j.1464-410x.2012.11280.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs open partial nephrectomy for T1 renal tumours: evaluation of long‐term oncological and functional outcomes in 340 patients

Abstract: What's known on the subject? and What does the study add?• Whereas open nephron-sparing surgery (NSS) represents the 'gold standard' in the surgical therapy of T1 renal tumours, with the advances in laparoscopic surgery, the refinement of intracorporeal suturing and the availability of haemosealant substances, the laparoscopic approach to NSS is increasingly used. Laparoscopic partial nephrectomy (LPN), however, is currently performed in just a few high-volume reference centres, and its diffusion has been limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 33 publications
3
44
0
1
Order By: Relevance
“…While the laparoscopic approach was associated with a significantly mean longer WIT, at multivariable analysis LPN was an independent predictors of a WIT [25 min. This is in line with most of the recent comparative studies between LPN and OPN, where LPN results constantly associated with a longer WIT, although some authors reported shorter WIT in their LPN series [6,7,18,19]. Consequently, in our LPN cohort a significantly higher eGFR variation on third postoperative day compared to the OPN cohort was observed.…”
Section: Discussionsupporting
confidence: 91%
“…While the laparoscopic approach was associated with a significantly mean longer WIT, at multivariable analysis LPN was an independent predictors of a WIT [25 min. This is in line with most of the recent comparative studies between LPN and OPN, where LPN results constantly associated with a longer WIT, although some authors reported shorter WIT in their LPN series [6,7,18,19]. Consequently, in our LPN cohort a significantly higher eGFR variation on third postoperative day compared to the OPN cohort was observed.…”
Section: Discussionsupporting
confidence: 91%
“…16 Similarly, Springer and coworkers, showing results from a retrospective singleinstitutional study of 340 open and laparoscopic PNs for cT1 RCC, found comparable incidence of PSMs between the 2 groups (1.7% vs. 1.2%; P ¼ .09). 24 It appears still controversial whether the age at the time of surgery could be a predictor of PSMs. In our report, the rate of positive margins was found to be slightly greater in patients older than 65 years, even if these data were not statistically significant at univariable analysis (Table 1; P ¼ .07).…”
Section: Riccardo Schiavina Et Almentioning
confidence: 99%
“…47 In a long-term study, Springer et al found no difference between LPN and OPN in postoperative eGFR at 5 years. 48 Similarly, in a study of RPN with intermediate-term follow-up, only an 8% mean decrease in postoperative eGFR was observed at a mean follow-up of 3 years. 49 Longer-term comparisons of functional outcomes for RPN with other surgical approaches are currently lacking.…”
Section: Outcomes Of Lpn Functional Outcomesmentioning
confidence: 99%
“…Similarly, Springer et al reported comparable 5-year overall survival (94% versus 91%) and cancer-specific survival (92% versus 88%) in patients undergoing LPN versus OPN, respectively. 48 In a study of 134 patients treated with RPN and followed for a minimum of 2 years, Khalifeh et al reported actuarial 5-year overall survival and cancer-specific survival rates of 90% and 99%, respectively. 49 Gupta et al similarly reported no local or metastatic recurrences following RPN at a median follow-up of 22 months.…”
Section: Oncologic Outcomesmentioning
confidence: 99%